2006
DOI: 10.1002/adsc.200600317
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Enantioselective [2+2+2] Cycloaddition of Diynes and Monoalkynes for the Generation of Axial Chiralities

Abstract: A highly enantioselective intermolecular [2 + 2 + 2] cycloaddition of alkynes was catalyzed by a chiral iridium complex. Symmetrical and unsymmetrical diynes, and monoalkynes possessing functional group(s) were subjected to the reaction and various types of axially chiral compounds possessing biaryl skeletons were obtained in good to excellent enantiomeric excesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 22 publications
0
22
1
Order By: Relevance
“…As expected, ees increased from 82 to 93% when lowering the temperature from 20 to -20°C (R = Ph). The origin of the enantioselectivity was attributed to cycloaddition of diynes with monoalkynes (reactions similar to those described in Scheme 7.4), they screened the influence of various parameters [216]. They observed that in most cases the temperature (rt to 100°C) and the nature of Z, Ar or R did not dramatically affect the ee value, underlying the robustness of the reaction.…”
Section: Co Catalystsmentioning
confidence: 93%
“…As expected, ees increased from 82 to 93% when lowering the temperature from 20 to -20°C (R = Ph). The origin of the enantioselectivity was attributed to cycloaddition of diynes with monoalkynes (reactions similar to those described in Scheme 7.4), they screened the influence of various parameters [216]. They observed that in most cases the temperature (rt to 100°C) and the nature of Z, Ar or R did not dramatically affect the ee value, underlying the robustness of the reaction.…”
Section: Co Catalystsmentioning
confidence: 93%
“…In 2004, they presented the first [2+2+2] cycloadditions of diynes with bis-propargylic partners, using a combination of [Ir(cod)Cl] 2 and (S,S)-Me-Duphos as catalytic system to obtain teraryl compounds with high enantio-and diastereoselectivities (Scheme 21). [51] Triynes also represent valuable candidates for this reaction, furnishing the corresponding atropoisomeric 1,2diarylbenzene derivatives with high yields and selectivities. [51] Triynes also represent valuable candidates for this reaction, furnishing the corresponding atropoisomeric 1,2diarylbenzene derivatives with high yields and selectivities.…”
Section: Iridium Catalysismentioning
confidence: 99%
“…Shibata et al reported iridium(I)/( S,S )‐MeDUPHOS catalyzed [2 + 2 + 2] cycloaddition of unsymmetrical diyne 30 gave an axially chiral biaryl 31 in a good yield and ee (entry 9) [8]. The bulkiness of substituents on the alkyne was very important.…”
Section: Construction Of Axial Chiralitymentioning
confidence: 99%